A risk evaluation method for ramping capability shortage in power systems. (15th October 2016) - Min, C.G.; Park, J.K.; Hur, D.; Kim, M.K.
Abstract: This paper describes a risk evaluation method for RC (ramping capability) shortage. Two major uncertainties in power systems are considered: failure of generating units and NLFE (net load forecast error). The failure probability of generating units is calculated using a Markov-chain-based capacity state model. The NLFE is assumed to follow a normal distribution, which is represented using a seven-step approximation. The risk of RC shortage is evaluated using an index termed the RSE (RC shortage expectation), which is defined as the sum of the probabilities that the RC requirement will be not satisfied by the system. A case study was then carried out using a modified IEEE-RTS-96 to investigate the applicability of the method. Sensitivity analysis was performed to determine the relationship between the RSE and the installed capacity of wind farms, the reserve requirement, and the failure rate of the largest unit. Highlights: A risk evaluation method for RC shortage was developed. The proposed method explicitly considers major uncertainties; i . e ., failure of generating units and net load forecast error. The risk of RC shortage is quantifiable using the proposed index, RSE (RC shortage expectation). A case study using a modified IEEE-RTS-96 demonstrates the applicability of the proposed method.